Zhuang Opera --- A study of Chinese Minority Arts in Guangxi Province, China (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article is a study of Zhuang Opera in the Guangxi Province in China. There are three general genres of Zhuang Opera, the analysis of selected musical pieces of these four types focuses on the music structure of Pingban melody, and the rhyme of the song texts --- Yaojiaoyun. This study is a pioneering work on the Zhuang Opera's musical form as there is currently no published work on the music of the opera and its association with related music categories. Except for very few research collections on national opera, most studies mainly focus on the history, literature, and folklore of traditional Zhuang Opera. In general, this study utilized new research methodologies producing different results from previous research, while at the same time, confirming earlier studies on the music and performance styles of the opera.